The different influence of leg extensors in development peak of force in drop jump - Vasiljev, R.; Dabovic, M.; Ilic, D. B. (ISB Congress, 2005)
The results of this study about the different influence of leg extensors in development peak of force in drop jump from a practical approach show: to improve impact jumping ability, depending upon stretch shortening cycle, improving a maximum strength should be a primary component of training programs rather than speed strength.